Operating speed of vehicles during rainfall at night: case study in Pontian, Johor - Hassan, Sitti Asmah (Penerbit UTM Press, 2016)
Speed is one of the important parameters of traffic flow that can be used to determine the performance of driver’s behaviour under various scenarios. Changes in weather conditions caused changes in drivers’ speed due to various reasons. In Malaysia, there is slightly high number of road accidents at night. Rainfall at night does not only cause poor visibility to drivers, but it also gives a sense of insecurity especially as there is a significant reduction in the visibility of the object in front. Improper road conditions can worsen the situation, for example, rainfall can cause water accumulation on road surfaces which can increase skidding problem, potholes and hydroplaning effect. In relation to these situations, hence it is crucial to understand how the abrupt situation affect response of driver’s in terms of the macroscopic behaviour. These unpredictable environmental changes seem like portraying a very unpleasant journey for drivers especially to travel under rainfall condition at night. Therefore, there is a need to observe how individual vehicles react in terms of speed adjustment and response to the different rainfall intensities downpour at night. Hence this study was conducted to determine the impact of different rainfall intensities at night on vehicles’ speed. Traffic data was obtained using automatic traffic counter at a cross section of a road at Pengkalan Raja, Pontian for about three months during monsoon season. Rainfall data report was obtained from the Department of Drainage and Irrigation, Pontian. From this study, it was found that there is a speed reduction from the dry condition regardless of rainfall intensities at night. As rainfall intensities at night higher, the speed reduction is higher as well except for heavy rainfall condition. The mean speed, 15th percentile and 85th percentile of vehicles decrease with the increase in rainfall intensity at night. It can be concluded that rainfall have impact on vehicle’s speed irrespective of their intensities. Findings from this study can be used to help local authorities and transport planners in planning an efficient traffic management system for a safer travel experience to road users in Malaysia.